Antidiabetic and renoprotective effects of cladophora glomerata kützing extract in experimental type 2 diabetic rats: A potential nutraceutical product for diabetic nephropathy - Srimaroeng,C. (Hindawi Publishing Corporation, 2015)
© 2015 Chutima Srimaroeng et al. Cladophora glomerata extract (CGE) has been shown to exhibit antigastric ulcer, anti-inflammatory, analgesic, hypotensive, and antioxidant activities. The present study investigated antidiabetic and renoprotective effects of CGE in type 2 diabetes mellitus (T2DM) rats. The rats were induced by high-fat diet and streptozotocin and supplemented daily with 1 g/kg BW of CGE for 12 weeks. The renal transport function was assessed by the uptake of para-aminohippurate mediated organic anion transporters 1 (Oat1) and 3 (Oat3), using renal cortical slices. These two transporters were known to be upregulated by insulin and PKCζ while they were downregulated by PKCα activation. Compared to T2DM, CGE supplemented rats had significantly improved hyperglycaemia, hypertriglyceridemia, insulin resistance, and renal morphology. The baseline uptake of para-aminohippurate was not different among experimental groups and was correlated with Oat1 and 3 mRNA expressions. Nevertheless, while insulin-stimulated Oat1 and 3 functions in renal slices were blunted in T2DM rats, they were improved by CGE supplementation. The mechanism of CGE-restored insulin-stimulated Oat1 and 3 functions was clearly shown to be associated with upregulated PKCζ and downregulated PKCα expressions and activations. These findings indicate that CGE has antidiabetic effect and suggest it may prevent diabetic nephropathy through PKCs in a T2DM rat model.